Informe sobre la identificación de un probador prometedor y métricas cuantitativas para el programa de mejoramiento de Megathyrsus maximus - Hernández, Luis Miguel; Castiblanco, Valheria (International Center for Tropical Agriculture, 2019)
With the overall aim to build the foundation of a breeding program for Megathyrsus maximus, during 2019 we formed the crosses required for the study of genetic parameters following a factorial genetic design. The structure of the crosses was the following, nine male-parent candidates where established in isolated plots to avoid pollen contamination. Once the males where stablished, thirty female parents were brought to the male plots. Cuttings in both parents where developed in order to promote and synchronize flowering, which has been the greatest challenge given that reproductive biology of the parents was largely unknown. The 30 female parents were identical (multiplication of them was clonal) for all nine male parent trials. During 2019, we were able to multiply parents in the glasshouse, stablish crossing plots and collect hybrid seed for eight out of nine crossing plots. During 2020, we aim to finalize crossing formation, develop post-harvest procedures, which involves also the time of dormancy and maybe (if budget allows it) identify within the progeny apomictic hybrids to be tested in the field in 2021.